2023
DOI: 10.26668/businessreview/2023.v8i3.1331
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Quality of Financial Reports

Abstract: Purpose: This study aims to determine the effect of the internal control system, information technology, applying of accounting standards, human resources competence, and the role of internal auditors on the quality of financial reports of local governments.   Theoretical framework: Internal control system, information technology, applying of accounting standards, human resources competence, and the role of internal auditors affect the quality of financial reports.  According to the agency theory, the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
0
0
0
Order By: Relevance
“…struggle with the lack of automation in this field and the lack of sales data insights that would enable them to create effective pricing plans and achieve the necessary growth while navigating the industry's difficulties (An, 2023). Airport managers are now looking into non-passenger revenue sources as well, such as land leasing, building theme-based activity arenas for tourists and locals, etc., as passenger numbers have significantly decreased as a result of COVID-19 (Anto, & Yusran, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…struggle with the lack of automation in this field and the lack of sales data insights that would enable them to create effective pricing plans and achieve the necessary growth while navigating the industry's difficulties (An, 2023). Airport managers are now looking into non-passenger revenue sources as well, such as land leasing, building theme-based activity arenas for tourists and locals, etc., as passenger numbers have significantly decreased as a result of COVID-19 (Anto, & Yusran, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we propose hypothesis: H3: Auditor tenure has a negative impact on state auditor's independence. Audit quality of SAI Audit quality is probability that auditor will find out a misstatement in auditee's accounting system and report the matter (DeAngelo, 1981) and it depends on the level of expertise of the auditor, while report will depend on auditor independence and competence (Anto & Yusran, 2023) . According to GAO (1986), audit quality is defined as compliance with professional standards and contractual terms for audit under consideration.…”
Section: The Relationship Between Relationship With the Auditee And S...mentioning
confidence: 99%
“…Hari & Bhavani (2015) showed that tangible means are the facilities' external image, the staff's attitude, documents, manuals, and banking communication systems. In general, everything that the customer can see directly with the eyes and senses can affect this factor (Anto & Yusran, 2023). Based on the above analysis, the authors propose hypothesis H5 as follows:…”
Section: Factors Affecting Thementioning
confidence: 99%